Answer:
- -32x² +8x -8
- See below about the process
Step-by-step explanation:
The simplified expression is ...
3x(x -12x) +3x² -2(x -2)²
= 3x(-11x) +3x² -2(x² -4x +4) . . . . . simplify contents of parentheses
= -33x² +3x² -2x² +8x -8 . . . . . . . .eliminate parentheses
= (-33 +3 -2)x² +8x -8 . . . . . . . . . . group the coefficients of like terms
= -32x² +8x -8
Answer: A
Step-by-step explanation:
A function is the comparing of two numbers all this is doing is multiplying two numbers.
Thats means angle BEC is 63. By the vertical angle theorem AED is the same. 3x-27 when x=30 is also 63.